Improving GSM Security By Enhancing Randomness Property Of A5/1 Design - Siti Yohana Akmal Mohd Fauzi; Kamaruzzaman Seman; Marinah Othman; Farrah Masyitah Mohd Shuib (AENSI Publisher, 2024)
Australian Journal of Basic and Applied Sciences, 9(32) Special 2015, Pages: 209-214